Characterisation of arsenic hyper-resistance in bacteria isolated from a South African antimony mine - Botes, Elsabé (University of the Free State, 2009)
Soil and water sites were sampled at a South African antimony mine with elevated levels of arsenic due to the refining process. Enriched media yielded six pure bacterial cultures able to grow in both arsenite and arsenate. These bacteria were identified as two strains of Bacillussp. (SA Ant 10(1) and SA Ant 14) with close relatedness to B. maltophilia and B. thuringiensis, another as Stenotrophomonas maltophilia SA Ant 15 and two isolates as Serratia marcescens (SA Ant 10(2) and SA Ant 16). Bacillus sp. SA Ant 14, S. maltophilia SA Ant 15 and S. marcescens SA Ant 16 were used for further investigation. All three isolates were able to grow in arsenite and arsenate respectively and S. marcescens SA Ant 16 grew in up to 500mM arsenate, making it the most arsenic resistant organism described to date. During growth, addition of arsenate or arsenite anions adversely affected biomass production and maximum specific growth rate and, in some instances, longer lag phases were induced. Reduction of arsenate to arsenite partly accounted for the high tolerance of the bacteria to arsenate. It was attempted to isolate the arsenate reductase from S. marcescens SA Ant 16 by making use of a PCR based approach using a both documented as well as degenerate primers based on sequence similarities of related Gram negative bacteria as well as Gram positive bacteria. After many unsuccessful attempts, this line of investigation was abandoned in favour of constructing genomic libraries. An Escherichia coliarsenate reductase knockout strain as well as a variety of laboratory strains was used for screening purposes. After screening of more than 5 x 104 colonies, no positive transformants were obtained. It may be possible that since S. marcescens SA Ant 16 exhibited hyper-tolerance to arsenate, the screening hosts used may not have been able to recognise and express the arsenate reductase from this organism successfully. The growth optima with regards to pH and temperature were established for S. marcescens SA Ant 16 grown under aerobic conditions as well as a suitable electron donor and electron acceptor concentration when grown under anaerobic conditions. The surface characteristics of S. marcescens SA Ant 16 cells, grown both in the presence and absence of oxygen, was investigated to infer adhesion capacity. It was found that both types of cells exhibited a negatively charged, highly hydrophilic and acidic character which would imply successful and similar adhesion of both aerobically and anaerobically grown cells to sand grains. Arsenate reduction was optimised in a factorial design layout with regards to electron donor (glucose) and substrate (arsenate) concentration under both aerobic and anaerobic conditions. Optimum contact time between cells and sand and loading capacity of the sand were determined. Cells were tracked through the sand columns and parameters for in situarsenate reduction established. Successful conversion of up to 50% arsenate to arsenite was demonstrated from an initial 5mM starting concentration. This hyper-resistant bacterium could be the solution to water contaminated with extremely high arsenate concentrations.

Grond en water monsters is versamel by ‘n Suid-Afrikaanse antimoon myn met hoë konsentrasies van arseen as gevolg van die herwinningsproses. Verrykte media het ses suiwer bakteriële kulture opgelewer wat in staat was om in beide arseniet en arsenaat te groei. Die bakterieë is identifiseer as twee stamme van Bacillus sp. (SA Ant 10(1) en SA Ant 14) met noue verwantskap tot B. maltophilia en B. thuringiensis, ‘n ander as Stenotrophomonas maltophilia SA Ant 15 en twee isolate as Serratia marcescens (SA Ant 10(2) en SA Ant 16). Bacillus sp. SA Ant 14, S. maltophilia SA Ant 15 en S. marcescens SA Ant 16 is gebruik vir verdere ondersoeke. Al drie isolate was in staat tot groei in beide arseniet en arsenaat en S. marcescens SA Ant 16 in tot 500mM arsenaat, wat dit die mees arsenaat weerstandbiedende organisme beskryf tot op hede maak. Gedurende groei het byvoeging van arsenaat of arseniet ione biomassa produksie en die maksimum spesifieke groeisnelheid negatief beïnvloed, en in sekere gevalle is langer sloerfases geïnduseer. Reduksie van arsenaat na arseniet kon gedeeltelik verantwoord vir die hoë weer stand van die bakterium tot arsenaat. Daar was gepoog om die arsenaat reduktase van S. marcescens SA Ant 16 te isoleer deur gebruik te maak van ‘n PKR-gebasseerde benadering met beide gedokumenteerde asook degenererende priemstukke gebasseer op basispaar ooreenstemmings van verwante Gram negatiewe en Gram positiewe bakterieë. Na vele onsuksesvolle pogings, is hierdie trant van ondersoek laat vaar ter wille van genomiese biblioteek konstruksie. ‘n Esherichia coliarsenaat reduktase delesiemutant asook ‘n verskeidenheid van laboratorium stamme is gebruik vir siftingsprosedures. Na sifting van meer as 5 x 104 kolonies is geen positiewe transformante verkry nie. Dit is moontlik dat as gevolg van die hiper-weerstandbiedendheid van S. marcescens SA Ant 16, die siftings gasheer nie die arsenaat reduktase van hierdie organisme kon herken en suksesvol uitdruk nie. Groei-optima met betrekking tot pH en temperatuur is vasgestel vir S. marcescens SA Ant 16 onder aerobiese toestande sowel as gepaste elektron-donor en elektron-akseptor konsentrasies vir groei onder anaerobiese toestande. Die oppervlak-eienskappe van S. marcescens SA Ant 16 selle, gegroei beide in die teenwoordigheid en afwesigheid van suurstof, is ondersoek om adhesie-kapasiteit af te lei. Daar is gevind dat beide tipes selle ‘n negatiewe lading, hoogs hidrofiliese en suur eienskappe het wat suksesvolle en eenderse adhesie van beide aerobies- sowel as anaerobies-gegroeide selle aan sandkorrels sou impliseer. Arsenaat reduksie is geoptimiseer in ‘n faktoriale ontwerp met betrekking tot elektron-donor (glukose) en substraat (arsenaat) konsentrasie onder beide aerobiese en anaerobiese toestande. Optimale kontaktyd tussen selle en sandkorrels sowel as ladingskapasiteit van die sand is bepaal. Selle is gevolg deur die sandkolomme en parameters vir in situarsenaat reduksie vasgestel. Suksesvolle omskakeling van tot 50% arsenaat na arseniet is gedemonstreer vanaf ‘n aanvanklike beginkonsentrasie van 5mM. Hierdie hiper-weerstandbiedende bakterium kan die oplossing wees vir water wat met uitermatig hoë konsentrasies van arsenaat besoedel is.
Thesis (Ph.D. (Microbial, Biochemical and Food Biotechnology))--University of the Free State, 2007
Keywords: Bacillus (Bacteria) -- Molecular genetics; Arsenic -- Environmental aspects; Bioremediation